lo g ( tan 1 ∘ ) + lo g ( tan 2 ∘ ) + ⋯ + lo g ( tan 8 9 ∘ ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Awesome!
x and y do not have to be integer and this would still work :)
Log in to reply
log(tanx) + log(tany) =log(tanx * tany) =log(tanx * tan(90-y)) as x+y=90; =log(tanx*cotx) =log(1) =0 so for any real x , y .
but in this ques only integer are used for this reason i was state as integer.
We should know the formulas tan ( 9 0 ∘ − A ∘ ) = cot A ∘ , lo g P + lo g Q = lo g ( P × Q ) . Also, you must know that tan θ × cot θ = 1 , tan 4 5 ∘ = 1 and lo g 1 = 0 . Now ----
lo g ( tan 1 ∘ ) + lo g ( tan 2 ∘ ) + . . . . . . . . + lo g ( tan 8 9 ∘ )
= lo g ( tan 1 ∘ ) + lo g ( tan 2 ∘ ) + . . . . . + lo g ( tan 4 5 ∘ ) + lo g ( tan ( 9 0 ∘ − 4 4 ∘ ) ) + lo g ( tan ( 9 0 ∘ − 4 3 ∘ ) ) + . . . . . . . + lo g ( tan ( 9 0 ∘ − 1 ∘ ) )
= lo g ( tan 1 ∘ ) + lo g ( tan 2 ∘ ) + . . . . . + lo g 1 + lo g ( cot 4 4 ∘ ) + lo g ( cot 4 3 ∘ ) + . . . . . . + lo g ( cot 1 ∘ )
= lo g ( tan 1 ∘ × cot 1 ∘ ) + lo g ( tan 2 ∘ × cot 2 ∘ ) + . . . . . . + lo g ( tan 4 4 ∘ × cot 4 4 ∘ ) + lo g 1
= lo g 1 + lo g 1 + . . . . . . . . + lo g 1 = 0 + 0 + . . . . . + 0 = 0
2ª line: wrong: log(tan(90º-44º)) ... correct: log(cot(90º-44º)) + log(cot(90º-43º)) + log(cot(90º-42º)) +....+ ...
Log in to reply
Please recheck your work: this solution is correct. Written succinctly, the solution is simply: k = 1 ∑ 8 9 lo g ( tan k ∘ ) = k = 1 ∑ 4 4 lo g ( tan k ∘ ) + k = 4 6 ∑ 8 9 lo g ( tan k ∘ ) + lo g ( tan 4 5 ∘ ) = k = 1 ∑ 4 4 lo g ( tan k ∘ ) + k = 1 ∑ 4 4 lo g ( tan ( 9 0 ∘ − k ∘ ) ) + lo g 1 = k = 1 ∑ 4 4 [ lo g ( tan k ∘ ) + lo g ( cot k ∘ ) ] + lo g 1 = k = 1 ∑ 4 4 lo g ( tan k ∘ × cot k ∘ ) + lo g 1 = 4 5 × lo g 1 = 0
I think you meant lo g ( tan 1 ∘ ) + lo g ( tan 2 ∘ ) + … + lo g ( tan 8 9 ∘ ) .
Anyway, apply the logarithm sum rule lo g a + lo g b = lo g ( a b ) to find lo g ( tan 1 ∘ ∗ t a n 2 ∘ ∗ … ∗ t a n 8 9 ∘ )
tan α = cot ( 9 0 ∘ − α ) → the tangent of an angle is equal to the cotangent of its complementary
So we have lo g ( cot 8 9 ∘ ∗ c o t 8 8 ∘ ∗ … ∗ t a n 8 9 ∘ )
Since tan α ∗ cot α = 1 , we find lo g ( cot 8 9 ∘ ∗ c o t 8 8 ∘ ∗ … ∗ t a n 8 9 ∘ ) = lo g ( 1 ) = 0
The reader knows that log(a)+log(b)=log(ab). We also know that tan(a)=cot(90-a) and tan(a).cot(a)=1 So, applying this in the problem, we get log(tan1.cot1.tan2.cot2.............tan45), (numbers are in degrees.) this turns out to be log(1) which is equal to "0"
here lo g ( tan 1 0 ) + lo g ( tan 8 9 0 ) = lo g ( tan 1 0 × tan 8 9 0 ) = lo g ( tan 9 0 0 tan ( 1 0 ) + tan ( 8 9 0 ) + 1 ) = lo g ( 1 ) = 0
And we can do the same thing with second term from beginning with the second term from last and third and so on. Now there are 1+89 = 90 terms and we can make 45 couples and each couple makes value of 0. So, sum up all the values, final answer is 0
we know tan ( A + B ) = 1 − tan ( A ) t a n ( B ) tan ( A ) + tan ( B )
So, tan ( A ) t a n ( B ) = tan ( A + B ) tan ( A ) + tan ( B ) + 1
be careful, tan 90 is undefined, it is better not to do it if limit is not taken
Since this is the addition of logarithms, an easy way to solve this is to first multiply all of the arguments. This would be log(tan1tan2tan3...tan89). Then, the tangent can be written as sine over cosine. This gives us log(sin1sin2sin3..sin89/cos1cos2cos3..cos89). Since sinx = cos(90-x), the terms can be cancelled out giving us log(1) which equals zero.
Best way to solve it is take log common and all the tan's inside will multiply and the result will be 1 like tan1 tan89=tan1 cot1=1 similarly solve all inside the bracket the we get the fianl value as log1 which is equal to 0
Problem Loading...
Note Loading...
Set Loading...
log(tanx) + log(tany) = 0 [where x , y both are integer & ( x + y = 90 )] and log(tan45) = 0 ; now try yourself .